The mechanistic role of antibodies to dengue virus in protection and disease pathogenesis. Issue 2 (1st February 2017) - Gan, Esther Shuyi; Ting, Donald Heng Rong; Chan, Kuan Rong
ABSTRACT: Introduction : Dengue is a prevalent disease in tropical and subtropical countries with an estimated 400 million people infected annually. While significant advancement has been made in the chase for an effective dengue vaccine, the recently licensed Sanofi vaccine was, in contrast to in vitro data, only partially protective. Areas covered : This suggests that our understanding of the serological correlates for dengue is currently inadequate. With growing evidence supporting the role of fragment crystalizable gamma receptors (FcγRs) in antibody-mediated neutralization or antibody-dependent enhancement (ADE) of dengue virus (DENV) infection, FcγR-expressing cells have been increasingly used for measuring neutralizing antibody responses elicited by dengue vaccines. Here, we review the mechanisms of how FcγRs modulates both DENV neutralization and enhanced infections via its interactions with antibodies. Expert commentary : This review provides insights on the importance of factoring FcγRs for in vitro neutralization assays. Bridging the gap between in vitro and clinical observations would allow researchers to more accurately predict in vivo vaccine efficacy.